Visual Basic for MS-DOS by example - Scott, D. F. (Carmel, Indiana : Que Corporation, 1992)
Provides step-by-step examples of programming in Visual BASIC, including using values and variables, writing instructions and groups, and working with modules, functions, form design, and other aspects of the language
Introduction -- Part 1. The Programming Environment -- Part II. Values and Variables -- Part III. Instructions and Groups -- Part IV. Modularization -- Part V. Arithmetic Functions -- Part VI. Form Design -- Part VII. The Screen -- Part VIII. Event Trapping -- Part IX. Data Management -- Part X. Appendixes -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: MS-DOS